2007
DOI: 10.5380/rsa.v8i2.8381
|View full text |Cite
|
Sign up to set email alerts
|

Produção De Biomassa E Rendimento De Óleo Essencial Em Camomila Cultivada Com Diferentes Doses De Cama-De-Aviário

Abstract: RESUMOO trabalho foi desenvolvido de março a novembro de 2006 no município de Campo Magro/PR, e teve como objetivo avaliar o rendimento de óleo essencial de camomila cv. Mandirituba e alterações no crescimento vegetativo e reprodutivo em função de diferentes doses de adubação com cama-de-aviário (0; 2,5; 5,0; 7,5; 10,0 e 12,5 kg m -2 ). O delineamento experimental foi em blocos casualizados, com seis tratamentos e quatro repetições, e cada parcela foi composta por um canteiro de 6 m 2 (2 x 3 m) com área útil d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 2 publications
0
4
1
3
Order By: Relevance
“…The yields of dried floral chapters for the March and April sowings are superior to those values obtained by Santos et al (2015) and Roza et al (2016) with the sowing performed in May, both in São José dos Pinhais -PR (451 and 615 kg ha -1 , respectively). The values are also superior to the yield found by Nalepa & Carvalho (2007), with the sowing performed in March in the municipality of Campo Magro -PR (471.8 kg ha -1 ). These results demonstrate that the chamomile sowing in Santa Maria exhibits a commercial production potential and may result in superior yields to those found by some authors in the state of Paraná, which presents the largest chamomile production area in Brazil (Corrêa Júnior & Scheffer, 2014).…”
Section: Resultscontrasting
confidence: 57%
“…The yields of dried floral chapters for the March and April sowings are superior to those values obtained by Santos et al (2015) and Roza et al (2016) with the sowing performed in May, both in São José dos Pinhais -PR (451 and 615 kg ha -1 , respectively). The values are also superior to the yield found by Nalepa & Carvalho (2007), with the sowing performed in March in the municipality of Campo Magro -PR (471.8 kg ha -1 ). These results demonstrate that the chamomile sowing in Santa Maria exhibits a commercial production potential and may result in superior yields to those found by some authors in the state of Paraná, which presents the largest chamomile production area in Brazil (Corrêa Júnior & Scheffer, 2014).…”
Section: Resultscontrasting
confidence: 57%
“…This may have occurred in the present study, since the collections with higher efficiency were obtained in the periods of lower precipitation. According to NALEPA & CARVALHO, (2007) another efficiency impairment may be the genotype. However, as in the present study the seedlings were acquired from a nursery and from these were made vegetative propagations of the other plants that were used as object of study, the authors do not believe this occurred.…”
Section: Extraction Efficiency Of Essential Oilsmentioning
confidence: 99%
“…The luminous intensity influences the concentration, as well as, the chemical composition of the essential oils. In the development of glandular trichomes, plant structures that biosynthesize and also store the essential oil, the presence of light is necessary (MORAIS, 2009). The greater biossynthesis of secondary metabolites under high levels of insolation is explained by the fact that biosynthetic reactions are dependent on the supply of carbon skeletons, performed by photosynthetic processes and compounds that participate in the regulation of these reactions (TAIZ & ZEIGER, 2009).…”
Section: Extraction Efficiency Of Essential Oilsmentioning
confidence: 99%
“…Kamada et al (1999) studying phenotypic plasticity in three accessions of basil, observed essential oil contents between 0.71 and 2.07%, and low values of heritability for this character, due to strong environmental influence. Nalepa;Carvalho (2007) mentioned that the essential oil content is genetically controlled, but it can be influenced by the external environment.…”
Section: Discussionmentioning
confidence: 99%